MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SD MELALUI MODEL PEMBELAJARAN KOOPERATIF QUESTION STUDENTS HAVE DAN FISHBOWL - Adam, Debby Tanti; Tauran, Sonya Fanny (Jurnal Padegogik, 2019)
Abstract: Mathematical communication is the ability of students to explain mathematical ideas both verbally and writing. But students' mathematical communication skills are still very low compared to other countries. The purpose of this research was to find out whether there were an increase in mathematical communication skills of students who obtained the cooperative learning model Question Students Have or Fishbowl type, and the students' responses to the learning model. The sample in this research were students of VA and VC, SD KARTIKA X-3 Parongpong, West Bandung. The instrument used is a mathematical communication skills test in the form of subjective questions related to the material "Collection and Presentation of Single Data". The statistical test used is a two-mean difference test, t-test at a significant level of 0.05. The results showed that (1) The increase of students' mathematical communication skills through cooperative learning models Question Students Have and Fishbowl types were in the medium category. (2) There is no significant difference in the increase of mathematical communication skills between students who get the cooperative learning model Question Students Have type and students who get Fishbowl type learning model. (3) Students' responses to mathematics learning using cooperative learning models Question Students Have type is in the "like" category while Fishbowl type is in the "really like" category. Keywords: Mathematical Communication, Cooperative Learning, Students Have Questions, Fishbowl